Effect of nano-silica coating combined with pressurized Ar treatment on postharvest quality and reactive oxygen species metabolism in sweet cherry fruit. (16th April 2022) - Meng, Xiangyong; Chen, Chang; Song, Teng; Xu, Jingwen; Zhang, Xiaobin; Wang, Jing; Pan, Zhongli; Zhang, Huien; Zhang, Huijuan
Highlights: Nano-silica coating and pressurized Ar enhanced antioxidant defense system in sweet cherries. Nano-silica coating and pressurized Ar reduced oxidative damage by scavenging of ROSs. Nano-silica coating and pressure Ar reduced decay incidence and maintained quality. Abstract: The mechanisms of effect of nano-silica coating and pressurized Ar on regulating reactive oxygen species (ROS) generation and scavenging in the senescence of sweet cherries remains unclear. The amounts of reactive oxygen species, hydrogen peroxide, non-enzymatic antioxidants and antioxidases, and cell membrane lipid peroxidation in sweet cherries were determined. Nano-silica coating, pressurized Ar, and the combination of these two treatments, all significantly delayed senescence by suppressing decay rate, and maintained good sensory quality. In additional, all treatments inhibited the generation and accumulation of superoxide anion and hydrogen peroxide, and mitigated the lipid peroxidation of cell membranes of sweet cherries. The combination of these two treatments maintained higher contents of ascorbic acid and glutathione, and enhanced the activities of antioxidases in sweet cherries. It is suggested that nano-silica coating and pressure Ar mediated the ROS metabolism, which might have a role in retaining the quality sweet cherries during cold storage.